The effect of sorghum fractions on apparent total tract digestibility and antioxidant capacity by dogs - Corsato Alvarenga, Isabella (PLoS One, 2018)
Sorghum is an abundant starch source that has many potential health benefits. Some pet food companies have adopted whole sorghum in their formulations, however sorghum flour and (or) its phenolic rich seed coat might provide added benefit to companion animal diets. The objective of this experiment was to evaluate diets utilizing sorghum flour (FLD), and sorghum mill feed (MFD) relative to whole sorghum (WSD), and conventional grains (rice, corn and wheat; CON) in a typical dog diet. Adult (1–3 yr) Beagle dogs (n = 12; 10.6 kg ± 1.4) were randomly assigned to individual pens with ad libitum access to water. Dogs were fed twice daily and adapted to diet (9 d), and then total feces were collected for 5 d over 4 periods in a 4x4 replicated Latin square design. Fecal output for determination of digestibility was estimated using Cr(2)O(3) as a marker. Number of defecations were quantified, and feces were scored. Approximately 3 mL of blood from each dog was collected at the end of each period and stored at -80° until further analyses. Means were separated using multivariate analysis of variance (MANOVA). Intake did not differ among treatments (average 187 g/d), but dogs fed the MFD excreted a larger (P<0.05) amount of feces, had more defecations per day, and lower (P<0.05) overall nutrient digestibility compared to the other treatments. The FLD had the highest (P<0.05) dry matter (DM), organic matter (OM), crude protein (CP) and gross energy (GE) digestibility, suggesting a possible application in “easy-to-digest” pet foods. Dogs fed the MFD had the highest (P < 0.05) plasma oxygen radical absorbance capacity (ORAC) value, but plasma ferulic and p-coumaric acids did not differ among treatments. Sorghum fractions have potential application in pet food; wherein, a bran rich fraction may promote antioxidant capacity, and flour increased digestibility.